Preparation of acylated blueberry anthocyanins through an enzymatic method in an aqueous/organic phase: effects on their colour stability and pH-response characteristics. Issue 15 (11th June 2021) - Zeng, Fansen; Zeng, HaiSheng; Ye, Yanqi; Zheng, Shiyu; Zhuang, Yuanhong; Liu, Jinna; Fei, Peng
Abstract : To explore the potential of anthocyanins in pH-colour responsive intelligent packaging and improve the stability of the pigments, 3, 4, 5-trimethoxybenzoic acid and gallic acid were grafted onto blueberry anthocyanins via enzyme-catalysed grafting. Abstract : To explore the potential of anthocyanins in pH-colour responsive intelligent packaging and improve the stability of the pigments, 3, 4, 5-trimethoxybenzoic acid and gallic acid were grafted onto blueberry anthocyanins via enzyme-catalysed grafting. The structural analysis based on UV-vis and IR spectroscopy showed that the two acids were successfully grafted onto the blueberry anthocyanins. The acylation degrees of the 3, 4, 5-trimethoxybenzoic acid-acylated anthocyanin (Tr-An) and gallic acid-acylated anthocyanin (Ga-An) were 6.38% and 6.51%, respectively. The results from the DPPH radical scavenging assay and ferric reducing antioxidant power assay implied that the antioxidant capacity of Tr-An was worse than that of natural anthocyanin (Na-An), but the antioxidant capacity of Ga-An was stronger than that of Na-An. The grafting of the two acids enhanced the stability of the blueberry anthocyanins and had little effect on the pH-colour response characteristics of the blueberry pigments.